2004
DOI: 10.1038/oby.2004.42
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal FABP2 A54T Polymorphism: Association with Insulin Resistance and Obesity in Women

Abstract: Research Methods and Procedures:According to a sampling scheme based on BMI, 33 adult obese women (BMI Ն 30) and 30 adult normal-weight women (BMI Ͼ 18.5 and Ͻ 25 kg/m 2 ) were recruited for this study. Women with chronic inflammatory diseases or acute pathology were excluded. Glucose, insulin, leptin, lipids, and tumor necrosis factor ␣ (TNF␣) were measured in fasting plasma samples. Insulin resistance was estimated through the homeostasis model assessment for insulin resistance method. The Ala54Thr allelic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 40 publications
3
39
0
5
Order By: Relevance
“…FABP2 plays a key role in absorption and intracellular transport of dietary long-chain fatty acids. Carriers of the Thr54 allele have a twofold greater affinity for long-chain fatty acids than those with the Ala54 allele which supports the role of the FABP2 Ala54Thr polymorphism in the etiology of metabolic disorders, such as insulin resistance [17] .…”
Section: Introductionmentioning
confidence: 72%
“…FABP2 plays a key role in absorption and intracellular transport of dietary long-chain fatty acids. Carriers of the Thr54 allele have a twofold greater affinity for long-chain fatty acids than those with the Ala54 allele which supports the role of the FABP2 Ala54Thr polymorphism in the etiology of metabolic disorders, such as insulin resistance [17] .…”
Section: Introductionmentioning
confidence: 72%
“…As shown in Figure 2C, four studies had a trend of elevated OR for the allele T (Albala et al, 2004;Takakura et al, 2005;Tavridou et al, 2009), and six studies showed a trend in the opposite direction (Lei et al, 1999;Ito et al, 1999;Carlsson et al, 2000;He, 2002;Duarte et al, 2003;Wang et al, 2011). No significant association was found between the FABP2 Ala54Thr polymorphism and obesity ( Figure 2C).…”
Section: A B Cmentioning
confidence: 99%
“…However, sib-pair analysis failed to detect any linkage of the FABP2 locus or the Ala54Thr polymorphism with diabetes-related phenotypes in other ethnic groups. The homozygous Thr54/Thr54 genotype has found the associations with higher fasting insulin levels and also TNF-α levels in 33 adult obese women (Albala et al, 2004). However, the findings of this study would need to be confirmed in studies involving a larger number of subjects.…”
Section: Impact Of Genetic Polymorphisms On Insulin Resistance 51mentioning
confidence: 44%